Debating terrorism and counterterrorism conflicting perspectives on causes, contexts, and responses - Gottlieb, Stuart (CQ Press, 2014)
Featuring paired pro/con pieces written specifically for this volume, this text encourages students to actively grapple with the central debates and questions surrounding the subject of terrorism and counter-terrorism.